1992
DOI: 10.1016/0735-1097(92)90015-f
|View full text |Cite
|
Sign up to set email alerts
|

Nonsurgical closure of femoral pseudoaneurysms complicating cardiac catheterization and percutaneous transluminal coronary angioplasty

Abstract: This study suggests that nonsurgical closure of femoral pseudoaneurysms is feasible. This technique may be valuable in managing vascular access-related complications after diagnostic and interventional procedures, even in patients requiring prolonged anticoagulant therapy.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
16
0
6

Year Published

1993
1993
2006
2006

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 63 publications
(22 citation statements)
references
References 22 publications
0
16
0
6
Order By: Relevance
“…Previous percutaneous nonsurgical closure of pseudoaneurysm has been achieved by direct intracavity injection of thrombin as well as transcatheter embolization, but these techniques are invasive and they had the same risks as direct surgical repair [23,24]. Incidences of vascular injuries after cardiac and vascular catheterization of 0.2-9% are reported in the literature [6,7,12,25,26]. Recent studies have shown a pseudoaneurysm rate of 1.6% after diagnostic catheterization and 0.7-6.3% after interventional procedures [3,[5][6][7]17,25].…”
Section: Discussionmentioning
confidence: 99%
“…Previous percutaneous nonsurgical closure of pseudoaneurysm has been achieved by direct intracavity injection of thrombin as well as transcatheter embolization, but these techniques are invasive and they had the same risks as direct surgical repair [23,24]. Incidences of vascular injuries after cardiac and vascular catheterization of 0.2-9% are reported in the literature [6,7,12,25,26]. Recent studies have shown a pseudoaneurysm rate of 1.6% after diagnostic catheterization and 0.7-6.3% after interventional procedures [3,[5][6][7]17,25].…”
Section: Discussionmentioning
confidence: 99%
“…Fellmeth et al [20,21] introduced ultrasound guided compression repair as a method for inducing thrombosis of the lesion by direct compression on the tract of the pseudoaneurysm. Subsequent reports [13,[22][23][24][25] confirmed a high success rate (93%-100%) and a low morbidity. Our study demonstrates the superiority of ultrasound guided compression over repeated compression bandages with a success rate of 87% versus 56% (P 5 0.016).…”
Section: Discussionmentioning
confidence: 88%
“…Von Kuster et al (1980) propose simple resection, while Martin and Manktelow (1982) and Rothkopf et al (1990) added a vascular reconstruction. More recently, treatment by compression, possibly guided by echography, has been favored for femoral aneurysms (Altkin et al 1989, Agrawal et al 1992, Feld et al 1992, Mac Glinckey and Baxter 1997. However, there are no recent reports on the treatment of ulnar pseudoaneurysms.…”
Section: Discussionmentioning
confidence: 99%